PENDIDIKAN ANAK SEBAGAI PROSES TAZKIYAT AL-NAFS: TELAAH PEMIKIRAN AL-GHAZALI DAN RELEVANSINYA BAGI MADRASAH IBTIDAIYAH - Muhammad Yusuf Septian (EBTIDA': Jurnal Pendidikan Dasar Islam, 2025)
This study interprets Al-Ghazali's main texts such as Ihya' Ulum al-Din, Ayyuha al-Walad, and Mizan al-'Amal to discover the essence of education from an Islamic spiritual perspective. The results of the study show that education in Al-Ghazali's view is an integral process between the development of reason, moral development, and purification of the heart. Teachers play a role not only as instructors, but as murabbi and ethical role models who guide students through exemplary behavior and sincerity. The relevance paradigm that balances intellectuality and spirituality, thus producing students who are knowledgeable, moral, and have pure souls.